2010
DOI: 10.2337/dc09-2254
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Glucagon in a Closed-Loop System for Prevention of Hypoglycemia in Type 1 Diabetes

Abstract: OBJECTIVETo minimize hypoglycemia in subjects with type 1 diabetes by automated glucagon delivery in a closed-loop insulin delivery system.RESEARCH DESIGN AND METHODSAdult subjects with type 1 diabetes underwent one closed-loop study with insulin plus placebo and one study with insulin plus glucagon, given at times of impending hypoglycemia. Seven subjects received glucagon using high-gain parameters, and six subjects received glucagon in a more prolonged manner using low-gain parameters. Blood glucose levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
188
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(198 citation statements)
references
References 19 publications
1
188
0
4
Order By: Relevance
“…The use of glucagon is not strictly speaking an MPC versus PID question, as glucagon can be used with PID control. Castle and coauthors 20 included glucagon in their fading memory proportional derivative controller ( Figure 2C, blue and light blue lines, with PID and MPC results from previous panels included for reference), albeit the fading memory proportional derivative algorithm does notas is evident in the name-include integral action. A discussion of the benefit of integral action is deferred until later in this report.…”
Section: Review Of Available Clinical Datamentioning
confidence: 99%
“…The use of glucagon is not strictly speaking an MPC versus PID question, as glucagon can be used with PID control. Castle and coauthors 20 included glucagon in their fading memory proportional derivative controller ( Figure 2C, blue and light blue lines, with PID and MPC results from previous panels included for reference), albeit the fading memory proportional derivative algorithm does notas is evident in the name-include integral action. A discussion of the benefit of integral action is deferred until later in this report.…”
Section: Review Of Available Clinical Datamentioning
confidence: 99%
“…Some research groups [26,[30][31][32] have developed feedback blood glucose control systems combining CSII and continuous glucose monitoring (CGM) that adjust subcutaneous insulin infusion rates based on blood glucose measurements obtained from a micro needle implanted subcutaneously. Most of the control methods utilized in these systems are model predictive control (MPC) and proportional, integral and differential (PID) control.…”
Section: Blood Glucose Control Systemsmentioning
confidence: 99%
“…However, the parameters of half-saturation glucagon amounts are fixed as constants of 10 -3 (k 3 [mg], from compartment 2 to compart- Model 7 has the same structure as Model 6 and replaces the linear transport from compartment 1 to compartment 2 with a Michaelis-Menten function (saturation at high doses). The Michaelis-Menten parameters are the maximal transport rate k 2 (mg/min) and the half-saturation amount k 3 (mg).…”
Section: Structures and Identification Of Glucagon Transport Modelsmentioning
confidence: 99%
“…More recently, glucagon has also been used in bihormonal artificial pancreas (AP) systems, where insulin and glucagon are both injected using subcutaneous (SC) pumps and dosed based on model prediction from continuous glucose monitoring data and history of injections. Castle et al 3 were the first to perform such a study and demonstrate that glucagon interventions can be successfully added to an AP system as a protection against hypoglycemia. Further studies were carried by El-Khatib et al 4 and Ward et al, 5 as well as the most recent randomized crossover trial by Haidar et al, 6 which also showed improvement of glucose control against hypoglycemia with nocturnal glucagon plus insulin closed-loop strategy over open-loop insulin infusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation